PARENTAL ACCEPTANCE OF PREMARITAL PREGNANCY AMONG UNDERAGE ADOLESCENTS IN TERMS OF RELIGION AND PSYCHOLOGY IN CINTA MAKMUR VILLAGE - LABUHANBATU - Sasmitha, Hesti; Siregar, Muhammad Habibi; Muttaqin, Farid (JURNAL AL-IJTIMAIYYAH, 2024)
Premarital pregnancy among underage adolescents is a complex and problematic social phenomenon in Indonesia. Cinta Makmur Village in Labuhanbatu is one of the case studies with a high prevalence. This study aims to understand parental self-acceptance of premarital pregnancy among underage adolescents in the village and the factors that influence it. This study uses a qualitative method with a case study approach. Data were collected through field observations, in-depth interviews with 2 pairs of parents who have teenage children who are pregnant premaritally, and documentation to support the research findings. The results of the study show that parental self-acceptance of premarital pregnancy among underage adolescents in Cinta Makmur Village varies. Some parents accept premarital pregnancy and try to help their children, while others reject and blame their children. Factors that influence parental self-acceptance include age, education, socioeconomic status, religious and cultural values, and social support. This study provides an important contribution to the understanding of parental self-acceptance of premarital pregnancy among underage adolescents in Indonesia. These factors need to be considered in efforts to prevent and manage premarital pregnancy among adolescents. The findings of this study can be used to develop intervention programs aimed at improving parental self-acceptance and reducing stigma associated with premarital pregnancy.